2000
DOI: 10.1053/eupc.2000.0124
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of continuous overdrive atrial pacing in atrial fibrillation

Abstract: Overdrive right atrial pacing has been used to prevent atrial fibrillation, but its efficacy in atrial fibrillation prevention and the patient tolerability and quality of life during high rate pacing remain uncertain. The objective of this study was to test the effects of a consistent atrial pacing algorithm that automatically paced the atrium at 30 ms shorter than the sinus P-P interval for atrial fibrillation prevention. Fifteen patients with sick sinus syndrome implanted with a Thera DR (model 7940 or 7960,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Another limitation is the fact that several previously examined algorithms [11,13] where used at the same time, which made it impossible to examine the contribution of a single prevention or treatment algorithm to the results obtained. The still widely used routine localization of atrial and ventricular leads were used to eliminate another possible influence on AT.…”
Section: Limitationsmentioning
confidence: 96%
“…Another limitation is the fact that several previously examined algorithms [11,13] where used at the same time, which made it impossible to examine the contribution of a single prevention or treatment algorithm to the results obtained. The still widely used routine localization of atrial and ventricular leads were used to eliminate another possible influence on AT.…”
Section: Limitationsmentioning
confidence: 96%
“…In general, mean heart rate is not significantly increased when these algorithms are working, and are well tolerated by the patients [36].…”
Section: Trigger Suppression Algorithmsmentioning
confidence: 99%
“…Dynamic atrial overdrive during short-term follow-up (FU) has shown a reduction in atrial arrhythmias, and demonstrating the feasibility and tolerability of the algorithm [5][6][7]. Overdrive suppression of atrial premature complexes which prevents postextrasystolic pauses reducing atrial ectopic activity, may also reduce atrial arrhythmias [8].…”
Section: Introductionmentioning
confidence: 99%